Synchronization of estrus in beef cows - Heekin, M.; Kiracofe, G.H.; Hultine, V.; Schalles, R.R.; McKee, R.M. (Kansas State University. Agricultural Experiment Station, 2011)
We used 79 cows to evaluate Syncromate B (G.D. Searle, Co.) as an estrus-synchronizing agent. Management of five groups of cows was: (1) nonsynchronized, bred naturally; (2) nonsynchronized, bred artificially; (3) synchronized, bred naturally; (4) synchronized, bred artificially at estrus; and (5) synchronized, bred artificially 60 hours after implant was removed. Conception rates were not affected by artificial breeding or synchronization. However, not all cows synchronized showed estrus. Percentages of cows bred during the first 25 days of the breeding season were 72.2, 71.4, 84.6, 68.7, 83.8 for groups 1 through 5, respectively.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Synchronization; Estrus; Artificial insemination; Natural breeding